2004
DOI: 10.1007/s00210-004-0975-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase C-mediated contraction by Rho kinase inhibitor fasudil in rabbit aorta

Abstract: Protein kinase C (PKC) activation by a phorbol ester increases myosin light chain (MLC(20)) phosphorylation through inhibition of MLC phosphatase (MLCP) and enhances contraction of vascular smooth muscle. We investigated whether Rho kinase, which is known to inhibit MLCP, is involved in the MLC(20) phosphorylation caused by a phorbol ester, 12-deoxyphorbol 13-isobutyrate (DPB), in rabbit aortas. DPB (1 microM) increased MLC(20) phosphorylation and tension. The Rho kinase inhibitor fasudil (10 microM) inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…In contrast to the consistent blocking effect of ONO‐RS‐082 on intracellular calcium signals in platelets (Francesconi et al 1995; Nakashima et al 1989; Tohmatsu et al 1989), the effects of ONO‐RS‐082 on intracellular calcium signals were nonhomogeneous in pancreatic acini (Nishino et al 1998; Tsunoda and Owyang, 1995). In VSMCs, ONO‐RS‐082 diminished receptor‐induced changes of [Ca 2+ ] i and subsequent calcium‐dependent phosphorylation of myosin light chains (Byron, 1996; Li et al 2001; Miura et al 1997; Shimomura et al 2004). All these effects of ACA and ONO‐RS‐082 were interpreted as PLA 2 ‐mediated responses due to the classification of both drugs as PLA 2 inhibitors.…”
Section: Pharmacologymentioning
confidence: 99%
“…In contrast to the consistent blocking effect of ONO‐RS‐082 on intracellular calcium signals in platelets (Francesconi et al 1995; Nakashima et al 1989; Tohmatsu et al 1989), the effects of ONO‐RS‐082 on intracellular calcium signals were nonhomogeneous in pancreatic acini (Nishino et al 1998; Tsunoda and Owyang, 1995). In VSMCs, ONO‐RS‐082 diminished receptor‐induced changes of [Ca 2+ ] i and subsequent calcium‐dependent phosphorylation of myosin light chains (Byron, 1996; Li et al 2001; Miura et al 1997; Shimomura et al 2004). All these effects of ACA and ONO‐RS‐082 were interpreted as PLA 2 ‐mediated responses due to the classification of both drugs as PLA 2 inhibitors.…”
Section: Pharmacologymentioning
confidence: 99%
“…Several studies indicate that there are interactions between Rho kinase and PKC, although the nature of the interaction remains in debate and may be cell type or agonist specific. Although Rho may be upstream of PKC activation in endothelial cells (21), in smooth muscle PKC has been shown to be upstream of Rho kinase activation (7,26,60). These findings were confirmed by in vitro kinase assays, which revealed that PKC is required for Rho activity (62).…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, it has a relaxant effect on vascular and myometrial smooth muscle (Domokos et al, 2017;Shimomura et al, 2004). Y-27632 was shown to reduce the voltage dependent potassium (Kv) channels and muscle tone in vascular smooth muscle (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%